Citronella is a promising crop for Sikkim Himalayas - Kalita, H; Babu, Subhash; Yadav, G S; Helim, R; Das, B (Indian Horticulture, 2019)
The economy of Sikkim mainly depends on agriculture which provides livelihood as well as productive engagement to the majority of the population. The agroclimatic conditions of the state provide ample scope for crop diversification and cultivation of aromatic plants in wastelands can pave a way for a better economy. The untapped potential of aromatic crops is now being promoted in Sikkim with the initiative of ICAR, Sikkim centre. Aromatic plants, viz. citronella, lemon grass and patchouli being grown in different districts of Sikkim are showing encouraging results. Cultivation and promotion of aromatic plants with improved production technology, post-harvest management and value addition is the need of the hour for crop diversification and has potential to boost up the economic scenario of the farming community of the state.